DASAR PERTIMBANGAN HAKIM DALAM MENJATUHKAN PIDANA PENJARA TERHADAP ANAK - Agus Indra Diandika, Made; Sudantra, I Ketut (Kertha Wicara : Journal Ilmu Hukum; Vol. 01, No. 05, November 2013)
The paper is titled "Basics of Criminal Justice In Jail Dropped Against Children". This paper uses analytical methods with normative juridical approach legislation. As for the legal issues that arise are the norm empty, because it is written in the criminal law has never found a rule that outlines the guidelines used by judges as a fundamental cornerstone consideration in the imposition of imprisonment, with the formulation of the problem what is the basis for consideration of the Judge in imposing imprisonment for child. Policies pursued by the government in response to criminal offenses committed by children is through the criminal law policy, which imposed sanctions such as prison punishment of the child. Judges in deciding criminal son, but must consider the legal aspects, which is proving the elements of an offense if the defendant has met and in accordance with the criminal offense of which the accused Prosecutor. Children in court proceedings, Judge consideration is the cornerstone or key principal that will produce decisions on criminal offenses committed by children . Then the conclusion of this paper is the judge in imposing imprisonment on children is by juridical considerations that interesting facts arising in the trial which is the conclusion of the testimony of the witnesses and the accused child's testimony and evidence presented and examined in court. Afterwards, the subjective judgment or conviction by Judge basis Moral Justice and Social Justice.
Keywords: Judge Consideration, Prison Punishment, Children